HUBUNGAN KEPATUHAN TERHADAP PROTOKOL KESEHATAN DAN DUKUNGAN KELUARGA TERHADAP KEJADIAN COVID-19 PADA MASYARAKAT DI KELURAHAN TANJUNG SENANG KOTA BANDAR LAMPUNG TAHUN 2021 - Rita Agustina; Dita Fitriani; Achmad Farich; Austine Widya Kusuma (Medula, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the SARS Coronavirus 2 (SARS-CoV-2). According to WHO data as of September 4, 2021, there were 218,946,836 confirmed cases and 4,539,723 deaths as a result of this virus. A considerable increase in the number of patients is frequently linked to noncompliance with community norms or indiscipline in applying health regulations. Aside from the level of community compliance, there are other factors that determine the occurrence of COVID-19, including family support. The family plays a significant role in developing and maintaining a fundamentally healthy lifestyle. However, many people are still unaware of the need of support from family members. The purpose of this study is to determine The purpose of this study is to examine the link between adherence to health protocols and family support on the incidence of COVID-19 in the Tanjung Senang Subdistrict of Bandar Lampung City in 2021. This study employs observational analytical quantitative research with a case control design. There is a significant link between Compliance with Health Protocols and the Incident of COVID-19, based on the statistical test findings of Compliance with Health Protocols and the Incident of COVID-19, with the p value = 0.000 (p0.05). Family Support and the Incident of COVID-19 received a p value of = 0.000 (p0.05), indicating that there is a significant association between the two. The incidence of COVID-19 is significantly related to adherence to health regimens and family support.